The use of shape analysis to differentiate between the mandibles of four economically important tephritid species. (25th October 2016) - Pieterse, W.; Manrakhan, A.; Ramukhesa, H. R.; Rosenberg, S. M.; Addison, P.
Abstract: The three fruit fly species (Diptera: Tephritidae) of economic importance that are most commonly intercepted during inspections of fruit for export at the Plant Quarantine Station of the Department of Agriculture Forestry and Fisheries in Stellenbosch, South Africa, are Ceratitis capitata, Ceratitis rosa and Ceratitis cosyra . A fourth fruit fly species of economic importance in South Africa which was recently declared present in the northern and north‐eastern parts of the country is Bactrocera dorsalis . Bactrocera dorsalis is absent in other areas of the country, including the Western Cape Province. The larval stage of fruit flies is the most commonly intercepted life stage, and identification of this stage using traditional morphological methods such as identification keys is difficult. This study investigates the use of shape analysis, a morphometric method, to identify the third instar larvae of four tephritid species commonly intercepted in fruit destined for export. Larval specimens of laboratory reared B. dorsalis, C. capitata, C. rosa s.s. and C. cosyra were used. The mandibles of third instar larvae of all species were dissected out, dehydrated and mounted in Euparal. Images of the mandibles were captured and analysed using elliptical Fourier descriptors (in the SHAPE v.1.3 analysis programme). According to the cumulative eigenvalues, the first two principal components (PCs) contributed the most (65%) to the shape change. The canonical variate analysis showed that the first PC separates C. rosa s.s. and C. cosyra from C. capitata and B. dorsalis . Ceratitis capitata and B. dorsalis were separated by the second PC. This study showed that morphometrics, in the form of shape analysis of the mandibles, can be used in combination with measurements of the mandibles to distinguish between third instar larvae of B. dorsalis, C. capitata, C. rosa s.s. and C. cosyra .